Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.5930
|View full text |Cite
|
Sign up to set email alerts
|

Ab1199 barriers and Facilitators to the Implementation of a Stratified Model of Care for Low Back Pain Patients in Primary Care in Portugal

Abstract: BackgroundThe results of a recent study have suggested that the current clinical practice is not in line with clinical guideline recommendations and may not be delivering the best outcomes to Low Back Pain (LBP) Portuguese patients. Since the stratified primary care approach has demonstrated clinical and cost-effectiveness in the UK and other countries, the SPLIT project aimed to introduce a similar approach that involves general practitioners (GPs) and physiotherapists (PTs) in the triage and targeted treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…Results from eight studies undertaken between 2011 and 2020 were included in the nal review and meta-synthesis. Authors were contacted to request full publications of two abstracts that appeared relevant to this review; one was not published (43) and one author contacted twice did not reply (44). In the eight articles retrieved, 76 physiotherapists and 65 GPs were interviewed or surveyed about their perspectives on the use of STarT Back.…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Results from eight studies undertaken between 2011 and 2020 were included in the nal review and meta-synthesis. Authors were contacted to request full publications of two abstracts that appeared relevant to this review; one was not published (43) and one author contacted twice did not reply (44). In the eight articles retrieved, 76 physiotherapists and 65 GPs were interviewed or surveyed about their perspectives on the use of STarT Back.…”
Section: Literature Searchmentioning
confidence: 99%
“…Four studies interviewed participants following exposure and use of STarT Back for several months (36,(45)(46)(47). The remaining four studies reported on interviewed participants who had completed workshops where potential STarT Back use was discussed (4,44,48,49).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations